2020
DOI: 10.37256/ser.122020140
|View full text |Cite
|
Sign up to set email alerts
|

Linking Teacher-Student Relationship to Academic Achievement of Senior High School Students

Abstract: Students’ level of academic engagement and achievement at any level of education is partly knit to the kind of relationships that exist between them and their teachers. The study examined the impact of teacher-student relationship on academic achievement of students in Senior High Schools in Winneba, Ghana. Eighty students were conveniently sampled from two strata whiles data was qualitatively collected using semi-structured interview guide and analyzed thematically. The study uses the four clusters of teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…By contrast, a negative teacher–student relationship can reduce students' interest, enthusiasm, and motivation for learning. If teachers often criticize students, shout at them, or are too strict with them, students would communicate less with their teachers and be unlikely to study hard (Opdenakker et al, 2012 ; Mensah and Eric Koomson, 2020 ). The findings of this study indicated that the better the teacher–student relationship, the stronger the students' academic motivation for the ideological and political subject in Chinese high schools.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a negative teacher–student relationship can reduce students' interest, enthusiasm, and motivation for learning. If teachers often criticize students, shout at them, or are too strict with them, students would communicate less with their teachers and be unlikely to study hard (Opdenakker et al, 2012 ; Mensah and Eric Koomson, 2020 ). The findings of this study indicated that the better the teacher–student relationship, the stronger the students' academic motivation for the ideological and political subject in Chinese high schools.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mensah and Koomson (2020) research, the type of relationship instructors has with their learners can sometimes be disincentive to learning. This new study agrees with Mensah and Koomson (2020) findings.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mensah and Koomson (2020) research, the type of relationship instructors has with their learners can sometimes be disincentive to learning. This new study agrees with Mensah and Koomson (2020) findings. According to the findings, the degree of instructors' closeness with learners can lead to learners paying less attention to their studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that the strong teacher-learner interpersonal relationship causes the intelligent learners to be successful in academic contexts. Mensah and Koomson (2020) asserted that learners who identify their educators as more helpful have academic achievement. They argued that teachers should be involved in communication with their learners in order to foster language learners' capabilities.…”
Section: The Effect Of Teachers' Interpersonal Behaviors On Learners'...mentioning
confidence: 99%